2013
DOI: 10.1007/978-3-642-40261-6_43
|View full text |Cite
|
Sign up to set email alerts
|

Motion Trend Patterns for Action Modelling and Recognition

Abstract: Abstract.A new method for action modelling is proposed, which combines the trajectory beam obtained by semi-dense point tracking and a local binary trend description inspired from the Local Binary Patterns (LBP). The semi dense trajectory approach represents a good trade-off between reliability and density of the motion field, whereas the LBP component allows to capture relevant elementary motion elements along each trajectory, which are encoded into mixed descriptors called Motion Trend Patterns (MTP). The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…On KTH (6 actions) we just obtain 91.1% recognition accuracy, which is not best but comparable to 91.7% in [27], 94.5% in [28] and 92.5% in [29]. It should be noticed that on this database those methods use a complex classifier or multiple descriptors combined to obtain better performance.…”
Section: Comparisons With Representative Algorithmsmentioning
confidence: 78%
See 1 more Smart Citation
“…On KTH (6 actions) we just obtain 91.1% recognition accuracy, which is not best but comparable to 91.7% in [27], 94.5% in [28] and 92.5% in [29]. It should be noticed that on this database those methods use a complex classifier or multiple descriptors combined to obtain better performance.…”
Section: Comparisons With Representative Algorithmsmentioning
confidence: 78%
“…Unified [32] 87.3% 93.6% Speech [33] 90.3% 96.2% SMT [27] 91.7% 93.4% HOG-OF [28] 94.3% 93.6% MTP [29] 92 …”
Section: B Comparisons With Other Bio-inspired Methodsmentioning
confidence: 99%
“…Furthermore, it achieves a trade-off between dense optical flow and long term point tracking, which makes it a very versatile brick that can be used in many different applications: non rigid object tracking, structure from motion, video stabilisation, video segmentation, action recognition and so on. It has been used already to build action descriptors using beam of trajectories [10,9]. In [9], it is shown that the performance of action classification is higher when the number of trajectory increases, up to a certain limit: when the quality of matching begins to drop.…”
Section: Discussionmentioning
confidence: 99%